John M. Lea, The Revised Laws of the City of Nashville, with the Various Acts of Incorporation and Laws Applicable to the Town and City of Nashville, and a List of the Different Boards of Mayor and Aldermen, and Other Officers of Said City from the Year 1806 to 1850, Inclusive Page 49, Image 50 (1850) [An Act to Reduce the Several Acts Incorporating the Town of Nashville in one act, and to Amend the Same, § 6. - (:unkn) unknown (My University, 1850)
§The Mayor and Aldermen shall have power, by ordinance within the city - ]25th. To regulate the storage of gun-powder, tar, pitch, rosin, salt-petre, gun-cotton, and all other combustible material, and the use of lights, candles and stove-pipes in all stables, shops, and other places.
Keywords: GUNPOWDER - STORAGE